THE SYNERGY OF ROLES AMONG FAMILY, SCHOOL, AND SOCIETY IN BUILDING CHILDREN'S MORAL IN A GLOBALIZATION ERA - Mochamad Iskarim (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
An era of globalization is characterized by the development of science and technology. This development contributes significant effects, including positive and negative ones. This study reveals that in fact, this kind of advancement causes several negative issues, particularly the decadence of the morality of nation’s generations. Relating to children’s morality, the unity among educational institutions is needed. Family as a small part of society is demanded to build religious values (morality) starting from the home. School as the other institution, attempts to integrate and to build the religious values through a well-systematized curriculum, as well as the role of society in controlling the moral building in daily lives.These three institutions, which affect one another, should possess synergy intensely when expecting the building of effective religious values to children in this era of globalization.